CITATION ANALYSIS OF JOURNAL OF NATURAL RUBBER RESEARCH, 1988-1997 - Tiew, W.S.; Kaur, K. (Malaysian Journal of Library and Information Science, 2000)
An analysis was carried out on 4181 citations appended to the References Section of 250 research articles and 8 short communications in Journal of Natural Rubber Research. It was found that journals/serial publications were the most cited source of information among rubber scientists (72.4%). The study also revealed the trend towards collaborative research among rubber scientists as two or more authors authored 61.56% of rubber literature. Rubber scientists are also quite up-to-date in their search for knowledge, as references cited were fairly recent with 55.97% covering the period of 1978-1997. The study also found that Rubber Chemistry and Technology toped the list (6.60%) as the most cited serial publication in the field of rubber research.